Double materiality in sustainability reporting: Revealing ESG-SDGs connections for businesses' awareness - Camelia Iuliana Lungu; Chirata Caraiani; Andreea Mădălina Bojan; Cornelia Dascălu; Raluca Andreea Achim (Amfiteatru Economic, 2025)
The aim of this research is to investigate the concept of double materiality embedded in sustainability reporting requirements that address both business and society perspectives. In light of stakeholder, legitimacy, and institutional theories, this document explores how environmental, social, and governance (ESG) policies and practices (financial materiality) included in a business strategy may be related to incentives for companies to prioritise Sustainable Development Goals (SDGs) (impact materiality). The data are collected from the Refinitiv Eikon database for nonfinancial international companies, over the 2015-2024 period. Parametric and nonparametric tests for differences in means, correlation analysis, and fixed effects robust regressions are employed to validate three research hypotheses. The results illustrate significant differences on financial and impact perspectives of materiality in European Union (EU) companies, as compared to non-EU companies. Strong associations between ESG scores and SDGs are identified and discussed using the double materiality approach. SDGs prioritisation in general, but also mapped for environmental, social, and governance, is found to have mixed impacts on ESG policies and practices. The findings support the hypothesis that prioritisation of the SDGs may ensure a balance among divergent interests of managers, investors, and other stakeholders. The study has academic and practical contributions to management decisions that integrate sustainable development goals to expand businesses' awareness of sustainability reporting requirements.
Keywords: M41; Q01; Q56; 330; double materiality; sustainability reporting; Environmental; Social; and Governance (ESG) policies and practices; Sustainable Development Goals (SDGs) prioritisation